Analisis Kesulitan Mahasiswa Pendidikan Agama Islam dalam Menyusun Perencanaan Pembelajaran Kurikulum Merdeka Belajar - Alfaien, Noor Isna; Kosim, Ahmad Mulyadi; Fadil, Khaidir; Husna, Miftahul (YASIN, 2025)
The implementation of Merdeka Belajar Curriculum requires Islamic Religious Education (PAI) students to be able to develop learning plans that are in accordance with the concepts and principles of the curriculum. However, in its implementation, students experience various obstacles in understanding learning outcomes, designing the flow of learning objectives, and developing teaching modules. This study aims to analyze the difficulties faced by PAI students in preparing lesson plans as well as strategies that can be applied by lecturers to overcome these obstacles. This study used a qualitative approach with descriptive method. Data were collected through interviews and observations of students who had taken microteaching courses at Ibn Khaldun University of Bogor. The results showed that students had difficulty in reading and understanding learning outcomes (CP), formulating learning objectives (TP), compiling a flow of learning objectives (ATP), and developing appropriate teaching modules. Strategies that can be done by lecturers to overcome this problem include intensive training, assistance in preparing learning tools, and hands-on simulations. With a more systematic approach, students can better understand the concept of learning planning in Merdeka Curriculum and improve their skills as prospective educators.